APPLICATION OF THE REGRESSION ANALYSIS METHOD FOR MODELLING THE PROCESSING OF LARGE AMOUNTS OF DATA - Toleugazy , Toleugazy R.T.; Balakayeva G.T. , Balakayeva (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
In the modern world, there is often a time when the relevance of actions is not necessary, in addition, there is a need to predict further stages of activity. All this is possible thanks to the use of regression analysis, which is used in many areas of activity. This article describes the application of this analysis to Bank risk, namely credit risk. Computational and theoretical studies on the processing of big data of banking institutions based on regression analysis, namely the method of multiple regression, have been carried out. In addition, this article provides a forecast based on various economic changes. This is very important for the banking sector, primarily because these studies reflect trends in credit risk.